Effect of optical losses irregularity on wideband fiber Raman amplification for total telecom window in silica fibers - Felinskyi, G.S.; Dyriv, M.Y.; Korotkov, P.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Raman threshold pump power and optical amplification band calculations
adjusted for attenuation dispersion in the range of total S+C+L telecom window of silica
fibers (roughly from 1.46 to 1.62 μm) are presented. It has been shown that wavelength
nonuniformity of signal attenuation coefficient essentially effects on amplification
bandwidth and leads to the bandwidth decrease from 0.9 to 2.5 THz depending on a
pump spectral position and fiber type. Offered has been the technique of analytical
approximation of attenuation coefficient as a basis for pump power threshold
determination and for preceding data correction with reference to an optical amplification
band. Simulation results for three widely used fibers, namely, DCF, TrueWaveRS™ and
SMF have been presented. However, the technique allows estimating the optimal pump
power in fiber Raman amplifiers for other fiber types as well.